2014
DOI: 10.1007/s00227-014-2546-z
|View full text |Cite
|
Sign up to set email alerts
|

New epizooic symbioses between sponges of the genera Plakortis and Xestospongia in cryptic habitats of the Caribbean

Abstract: dense Plakortis tissue. Symbioses with both Plakortis spp. were documented from an early recruit stage through adulthood. Spicule measurements conducted on symbiotic versus free-living X. deweerdtae revealed significantly smaller spicule sizes for symbiotic individuals, suggesting a cost in terms of silicon availability, or a benefit in terms of a lower investment in skeleton synthesis for support. This study reveals new specialized symbiotic associations between distantly related sponge genera that likely rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Samples of a sponge consortium constituted by Plakortis halichondrioides and Xetospongia deweerdtae specimens from Puerto Rico were collected by members of our research team at a depth of 90–100 ft. 24 The crude extract of a small portion of the consortium containing mainly Plakortis halichondrioides was extracted with CHCl 3 –MeOH. After solvent removal, the dark gum obtained was suspended in H 2 O and extracted exhaustively with n -hexane and CHCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of a sponge consortium constituted by Plakortis halichondrioides and Xetospongia deweerdtae specimens from Puerto Rico were collected by members of our research team at a depth of 90–100 ft. 24 The crude extract of a small portion of the consortium containing mainly Plakortis halichondrioides was extracted with CHCl 3 –MeOH. After solvent removal, the dark gum obtained was suspended in H 2 O and extracted exhaustively with n -hexane and CHCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…24 The organism was frozen and lyophilized prior to extraction. The dry specimens (395 g) were cut into small pieces and blended in a mixture of CHCl 3 –MeOH (1:1) (11 × 1 L).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that spicule morphology can be influenced by hypersilicification as a result of high silica concentrations (Maldonado et al, 1999). Sponges can also produce smaller spicules by living in association with other sponges (Vicente et al, 2014). In this study, higher silica concentrations from terrestrial runoff in habitats closer to the continental shelfs are likely the cause of larger oxeas in both N. dendrocrevacea sp.…”
Section: Discussionmentioning
confidence: 99%
“…argue that the symbiosis is life-long and does not cause mortality through smothering [23]. Biogeographic surveys have identified young recruits of P .…”
Section: Introductionmentioning
confidence: 99%
“…A more peculiar example of sponge-sponge epizoism is the symbiosis between Xestospongia deweerdtae and one of two possible basibionts: Plakortis deweerdtaephila or Plakortis symbiotica [ 23 , 24 ]. Sponges in the genus Plakortis are rich in cytotoxic secondary metabolites [ 25 29 ] and have been shown to swiftly kill neighboring organisms (e.g.…”
Section: Introductionmentioning
confidence: 99%